UMP staff resume working in the office in stages following CMCO - Nor Salwana, Mohammad Idris (2020)
Pekan, 22 May 2020 - Universiti Malaysia Pahang (UMP) will resume its operation in stages at all Responsibility Centres (Pusat Tanggungjawab, PTJ) starting 27 May through three attendance procedures during the Conditional Movement Control Order (CMCO) period.